Power system parameter matching and particle swarm optimization of battery underground loader. (October 2021) - Yi, Sheng-Xian; Yang, Zhong-Jiong; Zhou, Li-Qiang; Liu, Xiao-Yong
As part of the ongoing research into new energy technology, battery-powered underground loaders have emerged. However, there have been few studies on power system optimization and matching for these battery underground loaders to date. This paper, which takes a 3-m 3 battery underground loader as its research object, determines the loader's optimal operating point through study of the power response characteristics of the loader's motor under various working conditions. The effects of different power batteries on the working conditions are analyzed, and the loader's component parameters are matched. Additionally, an optimization model of the driving system of the battery underground loader is constructed. On the basis of the driving operation characteristics of the loader, the particle swarm optimization algorithm is proposed to optimize the operating conditions of the loader's driving motor. The results show that the transmission ratio is reduced after optimization. The single-cycle energy consumption is reduced by approximately 1.98% and the number of cycles in the health status of the power battery's state-of-charge increases by approximately 1.91%, which verifies the feasibility of use of the particle swarm algorithm in the loader optimization problem. This work can serve as a reference for related theoretical research on underground loaders.